ASUHAN KEPERAWATAN PADA ANAK DENGAN THALASEMIA DI PAVILIUN SERUNI RSUD JOMBANG - Adyanti, Handini Eky; Ulfa, Ana Farida; Kurniawati, Kurniawati (Jurnal EDUNursing, 2020)
Abstract Thalassemia is a disease of chronic that occur in children. Thalassemia is a disease abnormality of blood which is caused by disruption of production hemoglobin the body is reduced . The purpose of the literature study was to determine the nursing process in 4 respondents with thalassemia. The research design uses a literature study with case studies of nursing care in thalassemia patients in Seruni RSUD Jombang in the period 2014-2019. The results    of    the    study    literature     shows     that     problem     of     priority     patients     with thalassemia is perfused peripheral     not effective with a     decrease     in     concentration of hemoglobin. Literature study shows the results of the similarity of the causative factors in 4 respondents who experienced changes in tissue perfusion decreased hemoglobin concentration resulting in decreased O2 binding by erythrocytes so that blood flow to the peripheral tissues decreases and ineffective peripheral perfusion occurs which is characterized by patients feeling weak, conjunctival pallor , CRT> 2 seconds . Peripheral perfusion is not effective as a priority diagnosis because thalassemia patients experience abnormal red blood cell formation, in which blood cells rupture or lysis before 100 days, causing severe anemia that causes decreased  oxygen transport in cells. Keyword : Childcare Nursing, Thalassemia.